Vital Work: Adult Development Within the Natural Workplace - Terri A. Deems (Adult Education Research Conference, 1998)
This phenomenological study explores meaning and experience within the natural workplace. The educative potential is revealed through the organizations’ quest to nurture the human spirit at work and to create a more socially just work society. Findings illuminate conditions most conducive to growth and development within the context of work.